Implementasi Aplikasi Kepengaturan Dokumen Akreditasi Program Studi dengan Metode Borg and Gall - Ardhian Ekawijana; Bambang Wisnuadhi (JURIKOM (Jurnal Riset Komputer), 2022)
The Study Program Accreditation Document Arrangement Application is an application that helps to arrange accreditation supporting evidence documents. Accreditation is often a tiring job because all supporting evidence is scattered, both in physical or digital format. The focus of this research is on making your own application product. The research method is based on the Borg and Gall method. This method has several stages to make a product. The programming language used is NodeJS. NodeJS has a small execution time and is light, so it does not burden the user's device.The result of this research is in the form of an application, according to this method the results of this application have only reached the stage of Develop preliminary form of product.